Systematics, phylogeny and biogeography of genus Balkanopetalum Verhoeff, 1926 (Diplopoda: Callipodida: Schizopetalidae) - Stoev, Pavel; Enghoff, Henrik (Zootaxa, 2003)
The genus Balkanopetalum Verhoeff, 1926, is revised. The following species are recognised: B. armatum Verhoeff, 1926 (the type species), B. rhodopinum Verhoeff, 1937, B. beskovi Strasser, 1973, B. petrovi sp.n., B. bulgaricum sp.n., and B. graecum sp.n. All species, except B. graecum (Greece) are Bulgarian endemics. A very preliminary phylogenetic analysis suggests the following monophyletic groupings within the genus: (all species except B. rhodopinum); (beskovi + graecum + petrovi); (armatum + bulgaricum). The genus is near-endemic to the Rhodopi region which is probably also its area of origin.